Public libraries and Marxism - Pateman, Joe; Pateman, John, 1956- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Public Libraries and Marxism provides a Marxist analytical framework for understanding public libraries and presents a set of proposals for transforming the capitalist libraries of today. Evaluating the strengths and weaknesses of this Marxist framework, the authors also provide a critical examination of the history, theory and practice of libraries in the Soviet Union and North Korea. Considering what a Marxist library service would look like in the western capitalist countries of today, Pateman and Pateman synthesise the insights provided throughout the book into a set of Marxist proposals that are designed to promote the transformation of contemporary western public librarianship. These proposals suggest how western public libraries can change their organisation and practices - their strategies, structures, systems and culture - in order to best serve those with the most needs, particularly as society evolves in response to new challenges. Public Libraries and Marxism will be relevant for scholars and students of library and information science, history, politics and sociology. Outlining the rudiments of a Marxist library service that should be applicable around the world, the book will also appeal to library practitioners who want to develop libraries in a community-led and needs-based direction"--
Introduction -- The Marxist Interpretaton of the Public Library -- V.I. Lenin and Soviet Socialist Public Library System -- Kim Il-Sung and Socialist Public Libraries in North Korea -- The Vanguard Library -- Conclusion.
"Routledge Focus" -- Cover.
OCLC-licensed vendor bibliographic record.
Keywords: Public libraries -- Administration; Libraries and communism; Libraries -- Soviet Union -- History -- 20th century; Libraries -- Korea (North) -- History -- 20th century; Libraries and society; Critical theory; POLITICAL SCIENCE / Political Ideologies / Communism & Socialism; POLITICAL SCIENCE / Political Ideologies / General